2003
DOI: 10.4049/jimmunol.170.4.1641
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Apoptotic Tumor Cells to FcγR Provides Efficient and Versatile Vaccination Against Tumors by Dendritic Cells

Abstract: Dendritic cells (DCs) loaded with tumor-associated Ags (TAAs) act as potent adjuvant that initiates antitumor immune responses in vivo. However, TAA-based DC vaccination requires prior identification of TAAs. Apoptotic tumor cells (ATCs) can be an excellent source for DC loading because their potential uncharacterized Ags would be efficiently presented to T cells without any prior characterization and isolation of these Ags. However, ATCs alone are considered to be inefficient for activating antitumor immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 30 publications
2
89
0
Order By: Relevance
“…In addition, even when an attempt was made to increase protein uptake by the target cells, by forming immunocomplexes with specific antibody, there was no HTL proliferation to the PAX3/FKHR-loaded APC. This strategy of increasing protein uptake has proven to be effective in other studies [26,27]. And last, given the low concentration of peptide needed to stimulate HTL proliferation the lack of PAX3/FKHR protein in tumor cells most likely was not an issue in these experiments.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, even when an attempt was made to increase protein uptake by the target cells, by forming immunocomplexes with specific antibody, there was no HTL proliferation to the PAX3/FKHR-loaded APC. This strategy of increasing protein uptake has proven to be effective in other studies [26,27]. And last, given the low concentration of peptide needed to stimulate HTL proliferation the lack of PAX3/FKHR protein in tumor cells most likely was not an issue in these experiments.…”
Section: Discussionmentioning
confidence: 91%
“…5a). It has previously been demonstrated that incubating protein with an appropriate antibody can increase its uptake into PBMC [26,27]. The PAX3/FKHR vector contains a HIS tag.…”
Section: Htl Recognition Of Tumor and Pax3/fkhr Proteinmentioning
confidence: 99%
“…Most activating receptors associate with homodimeric subunits containing ITAM, such as the FcR common g chain and KARAP/DAP12 [15,16], and deliver positive signals into the cells through interaction with their ligands [17]. For instance, the uptake of immune complexes through activating FcR for IgG augments DC maturation, leading to efficient antigen presentation [18][19][20]. On the other hand, the inhibitory receptors harbor ITIM in their cytoplasmic portions and initiate inhibitory signaling by recruiting protein phosphatases, such as SHP-1 or SHIP, to phosphotyrosylated ITIM [13].…”
Section: Introductionmentioning
confidence: 99%
“…augments DC maturation, leading to efficient antigen presentation [18][19][20]. On the other hand, the inhibitory receptors harbor ITIM in their cytoplasmic portions and initiate inhibitory signaling by recruiting protein phosphatases, such as SHP-1 or SHIP, to phosphotyrosylated ITIM [13].…”
mentioning
confidence: 99%
“…There are s en DNA or m mplexes [8][9][10] or Cs by immatur l because they e antigen analy unknown num riginal immuni s is safe (elicit nity" [3] . Furthe ainst numerous ociated antigen age could comp [16,23] .…”
Section: Introductionmentioning
confidence: 99%